Pengaruh keperilakuan organisasi dan implementasi sistem akuntansi terhadap keuangan daerah (studi pada pemerintah Desa Tlekung Kota Batu) - Maria Savira; Ahmad Mukofi; Sri Andika (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
This study aims to determine the effect of organizational behavior and accounting system implementation on regional finances. The research was conducted on 30 respondents who have authority in the financial sector in the Tlekung Village Government, Batu City. The data used are primary data, which is obtained through distributing research questionnaires. In this study the research variables were grouped into two categories. The first is the independent variable consisting of organizational behavior and the implementation of the accounting system. The second is the dependent variable, namely regional financial accounting. To test the hypothesis, the quantitative data analysis method is used. Hypothesis testing tools used in the process of testing the hypothesis are multiple linear regression models, f-statistical tests and t-statistical tests. Based on the results of testing the first hypothesis, it was found that organizational behavior has a significant effect on the utility of regional finance in Tlekung Village, Batu City. The results of testing the second hypothesis indicate that the implementation of the accounting system has a significant effect on the usefulness of regional financial accounting in Tlekung Village, Batu City. Keywords: Behavioral, Organizational, Accounting systems, Regional finance